Perfecting your thinking skills : What is the best way for a modern executive to process information? : How do managers and business leaders gather and interpret information effectively? (MIT Sloan Management Review, 2018)
"Critical thinking -- meaning the ability to transcend bias and partial information to draw from objective analysis of facts to form a judgment -- is one of the more challenging skills for managers to cultivate. This collection of articles from MIT Sloan Management Review examines the ways to use data to supplement instinct, the importance of looking out for potentially important weak signals, and the ways to incorporate critical thinking into an organization overall."--Resource description page